Designing Large-Scale LANs - Dooley, Kevin (O'Reilly, 2002)
This unique book offers a vendor-neutral approach for designing large local area networks according to business or organizational needs, rather than from a product perspective. Author and independent network design consultant Kevin Dooley outlines ?top-down network design? for building a technological infrastructure to fit your organization's requirements, a process far more effective and cost-efficient than fitting the organization to the parameters of a shrink-wrapped proprietary solution. Dooley argues that the design of a network is largely independent of the products used. Whether you use a Cisco or Juniper router, the same security issues and protocols apply. The questions he addresses in this book are need-specific: Do I use a router or a switch? Should I route between switched areas or switch between routed areas? ?Designing Large-Scale LANs? covers everything from security, bandwidth and scalability to network reliability, which includes backup, redundancy, and points of failure. Specific technologies are analyzed in detail: network topologies, routing and switching strategies, wireless, virtual LANs, firewalls and gateways, security, Internet protocols, bandwidth, and multicast services. The book also discusses proprietary technologies that are ubiquitous, such as Cisco's IOS and Novell's IPX.